PERBEDAAN PERCEPATAN LAHIRNYA PLASENTA ANTARA POSISI TERLENTANG DENGAN POSISI ELEVATED RECUMBENT (SETENGAH DUDUK) - Fatimah, Virgin Norma; Murtiwi, Teten Tri; Puspasari, sri Yuni; Ulfah, Mariah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Abstract: Cases of haemorrhage in Cilacap General Hospital in May as many as 10 cases of 147 births. While the incidence of placenta retention 1 case of 147 births. Data June there were 4 cases of haemorrhage and placenta retention as much as 3 cases of 153 births, the average time of the birth of the placenta is 10 minutes. A total of 153 patients (100%) in the month of June 2013 the position of third stage of labor with the supine position. Objective : to know the difference acceleration of the birth of the placenta between supine position with elevated recumbent position in Cilacap General Hospital. Methods : The research used in this studi was a quantitative analysis of the Quasi experimental design with a sample of 66 women giving birth vaginally with inclusion criteria of gestational age > 20 weeks, not having retained placenta.Keywords: Third Stage Labor, Maternal Position In The Third Stage, Elevated Recumbent.